Current Treatment Options for Alzheimer's Disease and Parkinson's Disease Dementia - Szeto, Jennifer Y.Y. (Curr Neuropharmacol, 2016)
Alzheimer's disease (AD) and Parkinson's disease (PD) are the two most common neurodegenerative disorders encountered in clinical practice. Whilst dementia has long been synonymous with AD, it is becoming more widely accepted as part of the clinical spectrum in PD (PDD). Neuropsychiatric complications, including psychosis, mood and anxiety disorders, and sleep disorders also frequently co-exist with cognitive dysfunctions in AD and PDD patients. The incidence of such symptoms is often a significant source of disability, and may aggravate pre-existing cognitive deficits. Management of AD and PDD involves both pharmacological and non-pharmacological measures. Although research on pharmacological therapies for AD and PDD has so far had some success in terms of developing symptomatic treatments, the benefits are often marginal and non-sustained. These shortcomings have led to the investigation of non-pharmacological and novel treatments for both AD and PD. Furthermore, in light of the diverse constellation of other neuropsychiatric, physical, and behavioural symptoms that often occur in AD and PD, consideration needs to be given to the potential side effects of pharmacological treatments where improving one symptom may lead to the worsening of another, rendering the clinical management of these patients challenging. Therefore, the present article will critically review the evidence for both pharmacological and non-pharmacological treatments for cognitive impairment in AD and PD patients. Treatment options for other concomitant neuropsychiatric and behavioural symptoms, as well as novel treatment strategies will also be discussed.